Standardized, Interdepartmental, Simulation-Based Central Line Insertion Course Closes an Educational Gap and Improves Intern Comfort with the Procedure. Issue 6 (June 2017) - Grudziak, Joanna; Herndon, Blair; Dancel, Ria D.; Arora, Harendra; Tignanelli, Christopher J.; Phillips, Michael R.; Crowner, Jason R.; True, Nicholas A.; Kiser, Andy C.; Brown, Rebecca F.; Goodell, Harry P.; Murty, Neil; et al.
Central line placement is a common procedure, routinely performed by junior residents in medical and surgical departments. Before this project, no standardized instructional course on the insertion of central lines existed at our institution, and few interns had received formal ultrasound training. Interns from five departments participated in a simulation-based central line insertion course. Intern familiarity with the procedure and with ultrasound, as well as their prior experience with line placement and their level of comfort, was assessed. Of the 99 interns in participating departments, 45 per cent had been trained as ofOctober 2015. Forty-one per cent were female. The majority (59.5%) had no prior formal ultrasound training, and 46.0 per cent had never placed a line as primary operator. Scores increased significantly, from a precourse score mean of 13.7 to a postcourse score mean of 16.1, P < 0.001. All three of the self-reported measures of comfort with ultrasound also improved significantly. All interns reported the course was "very much" helpful, and 100 per cent reported they felt "somewhat" or "much" more comfortable with the procedure after attendance. To our knowledge, this is the first hospital-wide, standardized, simulation-based central line insertion course in the United States. Preliminary results indicate overwhelming satisfaction with the course, better ultrasound preparedness, and improved comfort with central line insertion.